Neutrophils as key drivers of pulmonary fibrosis: unveiling mechanisms and therapeutic implications - Liang, Xiuping; Li, Yanhong; Tang, Ziyi; Luo, Yubin; Liu, Yi (Frontiers in Immunology, 2025)
Pulmonary fibrosis is a chronic interstitial lung disease with an incompletely understood pathogenesis, and currently, effective treatment strategies remain elusive. Neutrophils, as pivotal effector cells of the innate immune system, are integral to the progression of pulmonary fibrosis. This review systematically examines the mechanisms by which neutrophils contribute to the advancement of pulmonary fibrosis through tissue infiltration, the release of neutrophil elastase (NE), and the formation of neutrophil extracellular traps (NETs). The interactions between neutrophils and other cell types, including alveolar macrophages, epithelial cells, and fibroblasts, create a complex inflammatory and fibrotic network. Clinical studies suggest that neutrophil levels and associated biomarkers, such as NET components, may serve as valuable indicators for disease assessment. Targeted therapeutic strategies, such as NE inhibitors, peptidyl arginine deiminase 4 (PAD4) inhibitors, blockade of the C5a-C5aR1 axis, and stem cell therapy, present promising avenues for the treatment of pulmonary fibrosis. This article aims to provide a comprehensive overview of the multifaceted roles of neutrophils in pulmonary fibrosis and their therapeutic implications.